Winners from the changing trends of energy intensities among 115 countries. (18th September 2020) - Chang, Yu Sang; Park, Nei Hei; Kim, Jin Bae
Many countries in the world have been experiencing vastly different rates of changes in their energy intensity (EI). The rate of change in EI for each country was estimated from the progress ratio (PR) of experience curve (EC). We ranked all 115 countries according to their PRs. The averaged PR of 90.21% estimated for the total 115 countries indicates a globally decreasing trend of EI. This means that each doubling of cumulative energy consumption has reduced energy intensity by 9.79%. On the other hand, 40 countries have experienced an increasing trend with an average PR of 119.41%. When two different types of EC, classical and kinked, were used, 81 countries displayed a kinked slope with an average PR of 84.98%. Analysing both the type of trend and slope of EC indicates that as many as 70 countries may have the best or better chances to improve their PRs in the future Implications from these findings will be discussed.